2006
DOI: 10.1093/jb/mvj206
|View full text |Cite
|
Sign up to set email alerts
|

Differential Enzymatic Characteristics and Tissue-Specific Expression of Human TPST-1 and TPST-2

Abstract: Protein tyrosine sulfation is emerging as a widespread post-translational modification in multicellular eukaryotes. The responsible enzyme, named tyrosylprotein sulfotransferase (TPST), catalyzes the sulfate transfer from 3'-phosphoadenosine 5'-phosphosulfate to tyrosine residues of proteins. Two distinct TPSTs, designated TPST-1 and TPST-2, had previously been identified. In the present study, we cloned human TPST-1 and TPST-2 expressed and characterized the recombinant enzymes using peptide substrates. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 40 publications
1
58
0
1
Order By: Relevance
“…This means that grt mice develop hypothyroidism and growth retardation because they are unable to fully respond to TSH (Sasaki et al 2007). It has been reported that TPST2 is ubiquitously expressed (Mishiro et al 2006). However, there has been no report concerning the expression of TPST2 in mouse pancreatic islets.…”
Section: Tpst2mentioning
confidence: 99%
“…This means that grt mice develop hypothyroidism and growth retardation because they are unable to fully respond to TSH (Sasaki et al 2007). It has been reported that TPST2 is ubiquitously expressed (Mishiro et al 2006). However, there has been no report concerning the expression of TPST2 in mouse pancreatic islets.…”
Section: Tpst2mentioning
confidence: 99%
“…The sulfate transfer is catalyzed by two independent tyrosylprotein sulfotransferases (TPST, 3′-phosphoadenylyl-sulfate:protein-tyrosine O -sulfotransferase, EC 2.8.2.20) (Lee and Huttner, 1983;Moore, 2003). The two TPST enzymes differ in their acidic pH optima, degree of stimulation by Mn 2+ and Mg 2+ (Mishiro et al, 2006) and have differential substrate affinities. Compared with TPST-2, TPST-1 exhibits significantly lower K m and V max for the majority of the substrates tested (Mishiro et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The two TPST enzymes differ in their acidic pH optima, degree of stimulation by Mn 2+ and Mg 2+ (Mishiro et al, 2006) and have differential substrate affinities. Compared with TPST-2, TPST-1 exhibits significantly lower K m and V max for the majority of the substrates tested (Mishiro et al, 2006). This is corroborated by the finding that in comparison to TPST-1, TPST-2 has a high degree of substrate preference towards the thyroid stimulating hormone receptor (Sasaki et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cell culture experiments, both TPST enzymes are capable of trypsinogen sulfation [20]. In the human pancreas, TPST2 is expressed at levels 50-fold higher than TPST1, indicating that physiological trypsinogen sulfation is mediated by TPST2 [18,21,22]. Notably, TPST2 expression is approximately 10-fold higher in the pancreas than in other human tissues.…”
Section: Introductionmentioning
confidence: 99%